Does Employment Density death? Towards a new integrated methodology to identify and characterize Sub-Centres - Jaume Masip Tresserra (European Regional Science Association (ERSA), 2012)
In last decades, the spatial structure of the metropolitan areas has been characterized by an urban dynamics towards a more polynucleated structure, breaking with the paradigm of the monocentric city. The specialized literature has studied these polynucleated urban structures by identifying the nuclei (sub-centres) that are within of the metropolitan areas. According to this objective, there are two approaches to identify sub-centres: by analyzing the employment or population density and by studying the mobility flows. Although, huge efforts have been done in the density approach, there are still some uncertainty points to solve: the density analysis could not identify and characterize simultaneously the sub-centres. That means distinguish those sub-centres that only attract workers (in-commuting flows) or retain their resident workers to those sub-centres that are able to attract flows and retain their resident employed population at the same time. In this paper, a new integrated methodology to identify and characterize simultaneously urban sub-centres is proposed by using an Employment Entropy function. In comparison with the density models, now it is possible to identify sub-centres and characterize them by "emerging" or "large-mature" by analyzing their Employment Entropy Information. In doing so, the Employment Entropy Information of each municipality is divided into two Entropy Information functions: the resident workers -RW- and the in-commuting flows -IF- Entropy Information functions. So, the paper is organized as following: firstly, the efficacy of the proposed methodology is tested in the Barcelona Metropolitan Region from 1991 to 2001 and secondly, the impact of these identified and characterized sub-centres on the urban spatial structure is studied by analyzing the evolution of polycentrism level and their influence on the urban hierarchy. The results suggest that in comparison with identifying sub-centres by using the standard density model, the municipalities identified as sub-centres by using "this double" Employment Entropy Information functions are more dominant in terms of in-commuting flows, more self-contained, and its influence on the urban structure are more significant, entailing a more polynucleated metropolitan structure.
Keywords: 330